Pengaruh E-LKPD Berbasis Android Materi Pembiasan dan Pemantulan Cahaya Terhadap Motivasi dan Hasil Belajar Fisika Peserta Didik - Rahmatullah Rahmatullah; Prelia Dwi Amanah; Fathoroni Fathoroni (Indonesian Journal of Teacher Education, 2022)
This study aims to determine the effect of using an Android-based Physics E-Student Worksheet (E-LKPD)—covering the topics of light refraction and reflection—on students' motivation and learning outcomes. A quasi-experimental method with a non-equivalent control group design was employed. The study sample consisted of a single class. A non-test instrument in the form of a response questionnaire was used to measure motivation, while learning outcomes were assessed using a multiple-choice test. Learning motivation was analyzed based on indicator achievement, whereas learning outcome data were analyzed using the N-gain test and hypothesis testing (t-test). The results indicate that the students' learning motivation fell into the high category, and an improvement in learning outcomes was observed. Hypothesis testing revealed a significant effect following the use of the Android-based E-LKPD. It is concluded that the use of the Android-based Physics E-LKPD has a positive impact on students' motivation and learning outcomes regarding the topics of light refraction and reflection.